Representations of the Natural World in Old English Poetry. - Neville, Jennifer (Cambridge Studies in Anglo-Saxon England, 27., 1999)
The author argues that Old English poetic descriptions of the natural world were not a reflection of physical conditions but a literary device used to define important issues, such as the state of humanity, the power of individuals and the relationship between God and creation.